2003
DOI: 10.1093/ndt/gfg210
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear leukocyte apoptosis in haemodialysis patients: the role of cell thiols and vitamin E

Abstract: This study showed an association between an increased apoptotic rate and decreased SHi in PBML of HD patients, but not of CAPD patients. These changes are partially due to different pro-apoptogens that accumulate in the plasma and are at least partially prevented by exogenous antioxidants able to restore SHi, such as vitamin E or thiol suppliers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…21 Although the exact mechanisms of inflammation and oxidative stress have not been accurately elucidated in CKD patients, a number of following described factors appear to be involved, including uremic toxins, 3 rennin-angiotensin system, 22 hypertension, 23 underlying diseases (diabetes, autoimmune diseases, etc. ), 24 infection, iron overload, 25 antioxidant deficiency, 26 etc. Oxidative stress can provoke inflammation via activating NF-kB and consequent generation of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although the exact mechanisms of inflammation and oxidative stress have not been accurately elucidated in CKD patients, a number of following described factors appear to be involved, including uremic toxins, 3 rennin-angiotensin system, 22 hypertension, 23 underlying diseases (diabetes, autoimmune diseases, etc. ), 24 infection, iron overload, 25 antioxidant deficiency, 26 etc. Oxidative stress can provoke inflammation via activating NF-kB and consequent generation of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These unfavorable phenomena exaggerate CRF-related complications, such as atherosclerosis and associated cardiovascular complications, accelerated ageing, β 2 -microglobulin arthropathy, defective deformability of erythrocytes, cataract, anemia, increased hemolysis and platelet dysfunction [1,2,3,4,5,6]. Such oxidative stress can also accelerate the apoptosis of leukocytes in hemodialyzed (HD) patients [7]. Numerous proteins are targets of oxidative stress as well [6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants (vitamin E) have been recently used in an attempt to improve biocompatibility of dialysis [8, 9, 32, 33]. Use of vitamin E-coated dialysis membranes, have been demonstrated to reduce levels of oxidative stress in PBMCs of patients undergoing hemodialysis [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…We and other investigators previously reported that dialysis membranes activate neutrophils to generate free radicals [6, 7]. Since free radicals have been reported to induce cell injury various investigators have recommended the use of vitamin E-coated dialysis membranes [8, 9]. …”
Section: Introductionmentioning
confidence: 99%